The losing-weight of elite's footballer: a case study - Rattanakoses, Raweewat; Soh, Kim Geok; Abdullah, Maria Chong; Omar Fauzee, Mohd Sofian (Human Resource Management Academic Research Society, 2012)
The purpose of study is to examine the affected of mental imagery and self-confidence of losing-weight on elite’ footballer by using the physical and mental practice. The subjects were elite footballer whom playing in Malaysian’ league (n=4). In the regular of this competition samples have training 5 days a week for three weeks, 8.00 A.M.-10.00 A.M. Researcher, had combine the activity in losing-weight into two concepts; losing-weight and mental practice. Data collection was mean and standard deviation for analyzing before and after losing-weight. Results shown that subject 1 was 1.8kg (5.4%), subject 2 was 3.8kg (4.3%), subject 3 was 2.6kg (3.0%), and subject 4 was 2.2kg (2.9%). And the imagery increased 16.7% (Subject 1), 15.9% (Subject 2), 12.5 % (Subject 3), and 6.0% (Subject 4), Self-confidence was increased 12.0% (Subject 1), 13.0% (Subject 2), 9.6% (Subject 3), and 3.8% (Subject 4) from baseline (single recorded). The finding of this study suggested that footballer had successfully by using imagery practice added during the physical training for losing weight. It helped them extract a problem of training such as boring, stress, and fatigue of training.